2020
DOI: 10.1029/2019ja027751
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study of the Enhancements in Ionospheric Electron Density and Its Longitudinal Gradient at Chinese Low Latitudes

Abstract: The day-to-day variability of the ionospheric electron density and its longitudinal gradient challenges our description and understanding of the ionosphere, which is also essential for reliable applications of the Global Navigation Satellite System (GNSS). In this paper we conduct a case study of the anomalous enhancements in ionospheric electron density and its longitudinal gradient to reveal the spatial extent and related drivers of the enhancements. The ionospheric data analyzed include the vertical total e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 29 publications
(42 reference statements)
1
16
0
Order By: Relevance
“…Recently Liu et al. (2020) conducted a case study of the anomalous enhancements in electron density at low latitudes in China, showing strong longitudinal and altitudinal gradients during the whole process of the enhancements. They suggested that equatorial zonal electric fields play an important role in forming the electron density enhancements at low latitudes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently Liu et al. (2020) conducted a case study of the anomalous enhancements in electron density at low latitudes in China, showing strong longitudinal and altitudinal gradients during the whole process of the enhancements. They suggested that equatorial zonal electric fields play an important role in forming the electron density enhancements at low latitudes.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, during geomagnetic storms the energy and energetic particles deposited in the polar upper atmosphere drive great changes in the chemical, electrodynamical, and thermodynamical processes in the whole ionosphere, and induce significant disturbances compared with the quiet time ionosphere (e.g., Buonsanto, 1999; Kuai et al., 2017; Lei et al., 2014; Liu et al., 2004; Mendillo, 2006; Prölss, 1995). Moreover, the ionospheric variations caused by lower atmospheric sources have also been studied in the past decades such as the ionospheric day‐to‐day variations (e.g., Depuev et al., 2008; Forbes et al., 2000; Huang et al., 2017; Liu et al., 2020, 2008; Mikhailov et al., 2009; Rishbeth & Mendillo, 2001; S.‐R. Zhang et al., 2005) or the anomalous changes during drastic meteorological events, such as sudden stratosphere warming (SSW) (e.g., Chau et al., 2012; Goncharenko et al., 2010; Liu et al., 2013, 2014, 2010; Matsuno, 1971; O'Neill, 2003; Pedatella & Liu, 2013; Yue et al., 2010; R. Zhang et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the similar occurrence climatology of two types of enhancement seems further support that the lower atmospheric forcing may modulate the ionospheric dynamo and cause the electric field eastward enhancement. The PEE seems belong to the “quiet‐time disturbance” (Q‐disturbance; David & Sojka, 2010; F. Huang et al., 2020; Kuai et al., 2021; L. Liu et al., 2020; Mikhailov et al., 2007; Zhao et al., 2008). However, like the prestorm enhancement of the electric field or EIA in the low‐latitude ionosphere (Burešová & Laštovička, 2007; Danilov, 2001; Danilov & Konstantinova, 2019; Kane, 1973; L. Liu et al., 2008; Mikhailov & Perrone, 2009), we still do not completely exclude the effects from the storm‐induced source.…”
Section: Observational Results and Discussionmentioning
confidence: 99%
“…Thus, the similar occurrence climatology of two types of enhancement seems further support that the lower atmospheric forcing may modulate the ionospheric dynamo and cause the electric field eastward enhancement. The PEE seems belong to the "quiet-time disturbance" (Q-disturbance; David & Sojka, 2010;Kuai et al, 2021;L. Liu et al, 2020;Mikhailov et al, 2007;Zhao et al, 2008).…”
Section: Occurrence Of the Daytime Eastward Electric Field Enhancementmentioning
confidence: 99%